2022
DOI: 10.1002/hbm.25874
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of the mood effects on third‐party responses to injustice after unfair experiences

Abstract: Behavioral decision theory argues that humans can adjust their third‐party responses (e.g., punishment and compensation) to injustice by integrating unfair experiences. Typically, the mood plays an important role in such a decision‐making process. However, the underlying neurocognitive bases remain largely unclear. We first employ a modified third‐party justice game in which an allocator split an amount of money between oneself and a receiver. The participants can reapportion the money as observers by choosing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
(116 reference statements)
1
6
0
Order By: Relevance
“…The MFC-IBS was positively correlated with behavioral coordination in the metrical context. Our fNIRS results are consistent with previous findings, in which the MFC-IBS was observed during scenarios involving social interaction, including decision-making ( Zhang et al, 2017 ; Xie et al, 2022 ), cooperation ( Hu et al, 2017 ; Feng et al, 2020 ), and communication ( Balconi et al, 2021 ). In particular in various cooperative activities, pairs of participants showed enhanced MFC-IBS in case of specific populations and tasks, such as professional athletes ( Li et al, 2020 ), expert teachers ( Sun et al, 2020 ), and less creative individuals ( Xue et al, 2018 ), and providing positive feedback ( Lu et al, 2019a ) and demanding divergent thinking ( Lu et al, 2019b ).…”
Section: Discussionsupporting
confidence: 92%
“…The MFC-IBS was positively correlated with behavioral coordination in the metrical context. Our fNIRS results are consistent with previous findings, in which the MFC-IBS was observed during scenarios involving social interaction, including decision-making ( Zhang et al, 2017 ; Xie et al, 2022 ), cooperation ( Hu et al, 2017 ; Feng et al, 2020 ), and communication ( Balconi et al, 2021 ). In particular in various cooperative activities, pairs of participants showed enhanced MFC-IBS in case of specific populations and tasks, such as professional athletes ( Li et al, 2020 ), expert teachers ( Sun et al, 2020 ), and less creative individuals ( Xue et al, 2018 ), and providing positive feedback ( Lu et al, 2019a ) and demanding divergent thinking ( Lu et al, 2019b ).…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the role of cognitive and emotional factors caused by encountering an injustice, such as perceptions of unfairness and anger, were not taken into account. Recent studies have found that negative emotional responses and unfairness perceptions of unfair distribution are associated with higher levels of rejection and punishment [ 61 , 62 ], so future research should explore how cognitive-emotional factors may impact this behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…However, they also involve distinct processes [ 5 ]. When facing injustice, both third-party responses correlate with the activation of fairness violations, e.g., the anterior insula (AI), anterior cingulate cortex (ACC), dorsolateral prefrontal cortex (DLPFC), striatal reward circuitry, and emotional regulation systems, including the amygdala and ventromedial prefrontal cortex (vmPFC) [ 5 , 20 ]. Enhanced ventral striatal activity is further associated with punishing an offender instead of helping a victim [ 5 ].…”
Section: Introductionmentioning
confidence: 99%